2023
DOI: 10.1101/2023.09.25.559307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ensembled best subset selection using summary statistics for polygenic risk prediction

Tony Chen,
Haoyu Zhang,
Rahul Mazumder
et al.

Abstract: Polygenic risk scores (PRS) enhance population risk stratification and advance personalized medicine, yet existing methods face a tradeoff between predictive power and computational efficiency. We introduce ALL-Sum, a fast and scalable PRS method that combines an efficient summary statistic-based L0L2penalized regression algorithm with an ensembling step that aggregates estimates from different tuning parameters for improved prediction performance. In extensive large-scale simulations across a wide range of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…L0Learn [21] , [25] , [27] has gained widespread recognition in bioinformatics research, with successful applications in haplotype reconstruction [47] , [48] , polygenic score (PGS) [49] , [50] calculation, and significant signal selection [51] , et. al.…”
Section: Discussionmentioning
confidence: 99%
“…L0Learn [21] , [25] , [27] has gained widespread recognition in bioinformatics research, with successful applications in haplotype reconstruction [47] , [48] , polygenic score (PGS) [49] , [50] calculation, and significant signal selection [51] , et. al.…”
Section: Discussionmentioning
confidence: 99%
“…The dominance of European populations persists in existing GWAS [50][51][52][53] , not limited to lung cancer and smoking cessation. However, with the burgeoning emphasis on incorporating minority populations in GWAS analyses and the development of new PRS approaches and toolkits to enhance predictive power in diverse populations [7][8][9]34,[54][55][56] , we can iteratively refine PRS implementation in our trial to synchronize with the latest advancements.…”
Section: Discussionmentioning
confidence: 99%
“…To address this gap, polygenic risk scores (PRSs) emerge as a valuable approach to assess disease susceptibility among populations and pinpoint individuals at higher risk [2][3][4] . PRSs can be derived from large-scale genome-wide association studies (GWAS) to estimate individual disease risk and have shown promise in predicting health outcomes and promoting preventive healthcare [5][6][7][8][9] . Despite their potential, PRSs' implementation in primary care is limited, especially in diverse populations.…”
Section: Introductionmentioning
confidence: 99%